High-throughput nanopore sequencing of Treponema pallidum tandem repeat genes arp and tp0470 reveals clade-specific patterns and recapitulates global whole genome phylogeny - Lieberman, Nicole A. P.; Armstrong, Thaddeus D.; Chung, Benjamin; Pfalmer, Daniel; Hennelly, Christopher M.; Haynes, Austin; Romeis, Emily; Wang, Qian-Qiu; Zhang, Rui-Li; Kou, Cai-Xia; Ciccarese, Giulia; Conte, Ivano Dal; et al. (Frontiers in Microbiology, 2022)
Sequencing of most Treponema pallidum (T. pallidum) genomes excludes repeat regions in tp0470 and the tp0433 gene, encoding the acidic repeat protein (arp). As a first step to understanding the evolution and function of these genes and the proteins they encode, we developed a protocol to nanopore sequence tp0470 and arp genes from 212 clinical samples collected from ten countries on six continents. Both tp0470 and arp repeat structures recapitulate the whole genome phylogeny, with subclade-specific patterns emerging. The number of tp0470 repeats is on average appears to be higher in Nichols-like clade strains than in SS14-like clade strains. Consistent with previous studies, we found that 14-repeat arp sequences predominate across both major clades, but the combination and order of repeat type varies among subclades, with many arp sequence variants limited to a single subclade. Although strains that were closely related by whole genome sequencing frequently had the same arp repeat length, this was not always the case. Structural modelling of TP0470 suggested that the eight residue repeats form an extended alpha-helix, predicted to be periplasmic. Modeling of the ARP revealed a C-terminal sporulation-related repeat (SPOR) domain, predicted to bind denuded peptidoglycan, with repeat regions possibly incorporated into a highly charged beta-sheet. Outside of the repeats, all TP0470 and ARP amino acid sequences were identical. Together, our data, along with functional considerations, suggests that both TP0470 and ARP proteins may be involved in T. pallidum cell envelope remodeling and homeostasis, with their highly plastic repeat regions playing as-yet-undetermined roles.